Enhancing effort supply with prize-augmenting entry fees : theory and experiments - Hammond, Robert G. (2021)
Entry fees are widely observed in contests. We study the effect of a prize-augmenting entry fee on expected total effort in an all-pay auction setting where the contestants' abilities are private information. An entry fee reduces equilibrium entry but can enhance the entrants' effort supply. Our theoretical model demonstrates that the optimal entry fee is strictly positive and finite. In a laboratory experiment, we empirically test the effect of entry fees on effort supply. Our results provide strong support for the notion that a principal can elicit higher effort using an appropriately set entry fee to augment the prize purse.